2012
DOI: 10.5483/bmbrep.2012.45.3.200
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory functions of purpurogallin in LPS-activated human endothelial cells

Abstract: Enzymatic oxidation of commercially available pyrogallol was efficiently transformed to an oxidative product, purpurogallin. Purpurogallin plays an important role in inhibiting glutathione S-transferase, xanthine oxidase, catechol O-methyltransferase activities and is effective in the cell protection of several cell types. However, the anti-inflammatory functions of purpurogallin are not well studied. Here, we determined the effects of purpurogallin on lipopolysaccharide (LPS)-mediated proinflammatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
27
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 31 publications
2
27
0
6
Order By: Relevance
“…(1) Herbal compounds could inhibit the binding and interactions of HMGB1 to its receptors. This concept was supported by the finding that herbal medicine blocks chemokine binding to its receptors [8][9][10][11][12][13][14]. (2) Herbal compounds could block the downstream signaling pathway of receptors activation by HMGB1; this is also supported by the finding that recently we showed that herbal compounds inhibited LPS-stimulated NF-κB activation which is the down-stream transcriptional factor of HMGB1 [8,11,[13][14][15][16][18][19][20][21][22].…”
supporting
confidence: 68%
See 1 more Smart Citation
“…(1) Herbal compounds could inhibit the binding and interactions of HMGB1 to its receptors. This concept was supported by the finding that herbal medicine blocks chemokine binding to its receptors [8][9][10][11][12][13][14]. (2) Herbal compounds could block the downstream signaling pathway of receptors activation by HMGB1; this is also supported by the finding that recently we showed that herbal compounds inhibited LPS-stimulated NF-κB activation which is the down-stream transcriptional factor of HMGB1 [8,11,[13][14][15][16][18][19][20][21][22].…”
supporting
confidence: 68%
“…We recently showed that herbal single compound down-regulated the cell surface expression of the three receptors, TLR-2, TLR-4, and RAGE, which are known to bind HMGB1 to initiate pro-inflammatory responses in endothelial cells [8][9][10][11][12][13][14]. Similar to HMGB1, LPS also upregulated the expression of all three receptors on endothelial cells, and single compound from herbal medicines down regulated this effect [8][9][10][11][12][13][14][15][16][17][18], suggesting that herbal compounds can inhibit the amplification of pro-inflammatory pathways propagated by LPS and HMGB1 during infections. There are several potential mechanisms by which herbal compounds could interfere with HMGB1 functions.…”
mentioning
confidence: 99%
“…Expression of vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and E-selectin on HUVECs was determined by whole-cell ELISA, as described previously [7,24]. Briefly, confluent monolayers of HUVECs were treated with TGFBIp (5 μg/ mL) for 6 h followed by each compound (20 μM) for another 6 h. The medium was removed, and cells were washed with PBS and fixed with 50 μL of 1 % paraformaldehyde for 15 min at room temperature.…”
Section: Expression Of Cams and Receptor Expressionmentioning
confidence: 99%
“…Expressions of vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), and E-selectin on HUVECs were determined by whole-cell ELISA, as described in previous studies [39,40]. Briefly, confluent monolayers of HUVECs were treated with HMGB1 (1 lg/mL) for 16 h followed by polyozellin (0-20 lM) for 6 h. The medium was then removed, and the cells were washed with PBS and fixed with 50 lL of 1 % paraformaldehyde for 15 min at room temperature.…”
Section: Expression Of Cell Adhesion Molecules (Cams) and Receptor Exmentioning
confidence: 99%